2014
DOI: 10.1002/jat.3079
|View full text |Cite
|
Sign up to set email alerts
|

Successful validation of genomic biomarkers for human immunotoxicity in Jurkat T cells in vitro

Abstract: Previously, we identified 25 classifier genes that were able to assess immunotoxicity using human Jurkat T cells. The present study aimed to validate these classifiers. For that purpose, Jurkat cells were exposed for 6 h to subcytotoxic doses of nine immunotoxicants, five non-immunotoxicants and four compounds for which human immunotoxicity has not yet been fully established. RNA was isolated and subjected to Fluidigm quantitative real time (qRT)-PCR analysis. The sensitivity, specificity and accuracy of the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
6
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 58 publications
1
6
0
Order By: Relevance
“…A critical gap in the application of Tier 0 screening is the availability of validated gene expression signatures (or biomarkers) that have been robustly tested across laboratories, human cell culture models, gene expression platforms, and experimental designs. Transcriptional signatures have been developed to predict organ toxicities including liver cancer (Uehara et al, 2011;Doktorova et al, 2013;Eichner et al, 2013;Thomas et al, 2013;Yamada et al, 2013;Melis et al, 2014;Romer et al, 2014), renal tubular injury (Minowa et al, 2012), hepatocellular steatosis (Sahini et al, 2014), and immunotoxicity (Schmeits et al, 2015). Fewer examples exist in which transcriptional signatures have been built and validated for prediction of molecular initiating events (MIE) or downstream key events (KE) in adverse outcome pathways (AOP); examples include biomarkers predicting MIEs for rodent liver cancer and steatosis (Oshida et al, 2015a(Oshida et al, , 2015b(Oshida et al, , 2015c(Oshida et al, , 2016a(Oshida et al, , 2016b and human endocrine disruption (Ryan et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…A critical gap in the application of Tier 0 screening is the availability of validated gene expression signatures (or biomarkers) that have been robustly tested across laboratories, human cell culture models, gene expression platforms, and experimental designs. Transcriptional signatures have been developed to predict organ toxicities including liver cancer (Uehara et al, 2011;Doktorova et al, 2013;Eichner et al, 2013;Thomas et al, 2013;Yamada et al, 2013;Melis et al, 2014;Romer et al, 2014), renal tubular injury (Minowa et al, 2012), hepatocellular steatosis (Sahini et al, 2014), and immunotoxicity (Schmeits et al, 2015). Fewer examples exist in which transcriptional signatures have been built and validated for prediction of molecular initiating events (MIE) or downstream key events (KE) in adverse outcome pathways (AOP); examples include biomarkers predicting MIEs for rodent liver cancer and steatosis (Oshida et al, 2015a(Oshida et al, , 2015b(Oshida et al, , 2015c(Oshida et al, , 2016a(Oshida et al, , 2016b and human endocrine disruption (Ryan et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…A critical gap in the application of this approach is the availability of validated gene expression signatures that can be used to predict a chemical's mode of action, or the probability that the chemical induces specific toxicities, that have been robustly tested across laboratories, cell culture models (including human models), gene expression platforms, and experimental designs. Although many studies have published transcriptional signatures to predict various toxicities [Uehara et al, ; Minowa et al, ; Cheng et al, ; Doktorova et al, ; Eichner et al, ; Thomas et al, ; Yamada et al, ; Melis et al, ; Romer et al, ; Sahini et al, ; Wei et al, ; Oshida et al, ; Schmeits et al, ; Shen et al, ], these have not been extensively validated or applied, and the majority of this work has been done on rodent cells or tissues. Therefore, accepted signatures capturing diverse toxicological targets and effects in human cells are needed for development of effective chemical screening approaches.…”
Section: Introductionmentioning
confidence: 99%
“…These findings are in agreement with the recently published results from our lab that 200 nM of TBTO treatment downregulated the expression levels of genes involved in rRNA and tRNA processing and ribosome biogenesis in Jurkat cells (Schmeits et al, 2014). The present study further demonstrated…”
supporting
confidence: 94%